Histopathology of Gills Fish in Rivers Contaminated by Heavy Metals from Artisanal Gold Mining Waste in Lebong Regency, Bengkulu Province - Lestari, Dian Fita; Vestidhia Yunisya Atmaja; Santi Nurul Kamilah; Eliza Febrianti; Farisa Retno; Hengki Turnando; Ibranio Risditama (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
The aquatic environment is crucial for fish survival because fish require appropriate aquatic environment. Artisanal gold mining generates heavy metal waste in Lebong Regency, polluting the river flows. Heavy metals released into the aquatic environment generate water pollution problems due to their toxicity, persistence, and bio-accumulation in organism. The aim of this study was to investigate the histology of fish gill organs in the river contamined by heavy metals. Fish samples were taken by purposive sampling. Histological sections using the paraffin method and hematoxylin-eosin staining. The result of mercury detected in water is 0.01mg/L, exceeded maximum limit in river based on class II water quality standard (0.002mg/L). Histopathology of gills H. nemurus and T. Tricopterus fish (HAI scores <20) showed slight alterations such as epithelial lifting, secondary lamella fusion, and hyperplasia. Rasbora sp., M.circumcinctus, and O.niloticus gills fish (HAI scores>100) had severe irreversible damage, marked by telangiectasis at the tips of the secondary lamella. This is due to the presence of heavy metal contaminants in the water, that causes histopathological damage to fish gills. Parasitic infections were also discovered in some fish gills, impairing their function for respiratory and excretory organs which can be caused by low water quality.